Perspectives on barriers to implementing WHO’s five keys to safer food in resource-limited rural areas of developing countries - Batch, Vitowe; Kress, Martina; Gama, Aggrey Pemba; Ng’ong’ola-Manani, Tinna; Chiutsi-Phiri, Gabriella; Corner, Ponyadira Leah; Kumwenda, Save; Kaonga, Chikumbusko; Kamndaya, Mphatso; Monjerezi, Maurice; Leslie, John F.; Matumba, Limbikani (Frontiers in Nutrition, 2025)
Food contamination is a critical global health issue, with the WHO estimating millions of deaths and Disability-adjusted life years (DALYs) lost annually due to foodborne diseases, particularly in developing countries. To address this, the WHO introduced the Five Keys to Safer Food (WHO-FKSF) to promote essential food safety practices. We analyzed the limitations of the WHO-FKSF for use in developing countries. We explore contextually relevant adaptations, such as community engagement, infrastructure improvements, and innovations like durable, child-resistant tippy taps (simple, low-cost handwashing devices that dispense water when tipped) for handwashing, required to make the WHO-FKSF applicable in rural portions of developing countries. Addressing cultural norms and involving men in water-related tasks can further align food safety practices with everyday realities. We recommend providing a specific rationale for each actionable step, beyond the general reasoning provided for the five keys themselves. This additional information will improve comprehension and adherence to the practices. We also recommend revising Key 4, “Keep food at safe temperatures,” to “Store food safely” to better accommodate the lack of refrigeration and to promote low-cost food preservation methods. Adapting the WHO-FKSF to the specific needs of these communities could significantly reduce foodborne illnesses and improve public health outcomes across sub-Saharan Africa.